The effect of television media on beginner voters’ political participation - Hutasoit, Kennorton; Gusfa, Henni (Jurnal Studi Komunikasi, 2020)
The political participation of beginner voters in the 2019 Indonesian General Elections in Belu Regency, East Nusa Tenggara Province (NTT) differentiate the current research from other studies. The television media were assumed to influence the political participation of beginner voters in the border region. Correlation test (r) was used to uncover the findings of this study. This study revealed a correlation between exposure to television mass media and political participation with 0.623 value, or strong correlation level category. Television media exposure also had a significant influence on political participation in the border district. Therefore, television broadcasting institutions which manage public frequencies play an important role in increasing the political participation of beginner voters at the border district by broadcasting political and election-related contents or programs.